Web Services Composition Mechanisms: A Review - Garriga, Martín (2015)
Web Service composition is becoming the most promising way for business-to-business systems integration. However, current mechanisms for service composition entail a trade-off on multiple and complex factors. Thereby, existing solutions based on business Web Services, semantic Web Services, or the recent RESTful services, lack of a standardized adoption. This paper gives an overview of current approaches according to a set of features. Moreover, related core problems and future directions of service composition mechanisms are pointed out.